Pemodelan Sistem Informasi Pengelolaan Surat Pengantar Rujukan pada Rumah Sakit Menggunakan BPMN - Dudi Awalludin; Yudha Indrawan; Rini Malfiany (Jurnal Manajemen Informatika (JAMIKA), 2022)
A referral letter management system at the hospital has to be good because a referral letter is a letter from medical personnel/service providers to the hospital. The management of a referral letter is routinely done using spreading a form letter the referral of some hospital to the doctor or service providers manually, and so when the pain that the reference received from the doctor or service providers manually through a patient or the patient family. The purpose of the modeling of the information system for the management of the referral cover letter is to produce a design or model which can then be used to develop a computer-based referral letter management information system, with the development of an information system that is expected to increase the number of referrals from clinics to hospitals and will reduce the use of printed referral cover letters so that there is no need to distribute printed referral cover letters. The system development method is the System Development Life Cycle (SDLC) with the Waterfall model. Business Process Modelling management information system a referral letter it uses Business Process Modelling and Notation (BPMN).